Role of Candidate Genes Regulating Uterine Prostaglandins Biosynthesis for Maternal Recognition of Pregnancy in Domestic Animals. (19th May 2013) - Kumar, Rohit; Ramteke, P. W.; Nath, Amar; Pramod, R. Kumar; Singh, Satyendra P.; Sharma, Sanjeev Kumar; Kumar, Sandeep
Abstract : The survivability and opportunity of successful development of an embryo are influenced directly or indirectly by factors controlling uterine microenvironment. Out of all factors, hormones such as prostaglandins (PGs) released during the preimplantation period influence molecular interactions involved in maintenance of pregnancy through reciprocal interactions between the conceptus and endometrium. PGs are important regulators of female reproductive functions, namely, ovulation, uterine receptivity, implantation, and parturition. Among different classes of PGs, prostaglandin F2 α (PGF2 α ) and prostaglandin E2 (PGE2) are main prostanoids produced by human and bovine endometrium for successful growth and development of the posthatching blastocyst. In ruminants, PGF2 α produced by endometrium is the major luteolytic agent, whereas PGE2 has luteoprotective and antiluteolytic properties. Therefore, the development and maintenance of the corpus luteum (CL), as well as establishment of pregnancy, depend on the balance of luteolytic PGF2 α and luteotropic PGE2. In this review, we discussed the expression and function of genes which predominantly regulate the synthesis and their secretion of PGF2 α and PGES, namely, PGFS (AKR1B5/AKR1C3), PGES, PGFR, and COX-2.